PENGARUH VARIASI UMPAN TERHADAP KEPADATAN LALAT PADA PERANGKAP BOTOL PLASTIK AIR MINERAL - Sulasmi Sulasmi; Eka Ayu Astuti; La Taha La Taha (Politeknik Kesehatan Kemenkes Makassar, 2023)
Flies are a type of nuisance insect. Flies’ activity is influenced by sunlight, temperature, humidity, water, food and breeding areas. Flies are able to produce quickly which is as long as 15 days. They are vectors of foodborne diseases including dysentery, diarrhea, vomiting, typhoid and some species could cause myiasis. Flies could not be completely wiped out but it can be controlled to less dangerous and harmless level. The aim of this research is to determine the effect of decoy variations on the density of flies in plastic bottle traps of mineral water. This research is a Quasi-experimental study using a Post Test Only With Control Group research design. By using this research design, it is possible to measure the preference for the type of decoy that being used. The sample used in this research was all flies caught in plastic bottle of mineral water and the data analysis will be tested by performing statistical tests. The results of the One way ANOVA test showed a significant value of p = 0.000 < α0.05, this means that there is an influence of decoy variation on the density of flies, brown sugar decoy is the the one that attracts and catch flies the most. It can be concluded that there is an effect of decoy variations on the density of flies in plastic bottle traps of mineral water. researchers suggest that traders in the market can use plastic bottle traps of mineral water to reduce the flies density.